2017
DOI: 10.5539/ijef.v9n2p15
|View full text |Cite
|
Sign up to set email alerts
|

Forecasting Volatility Stock Return: Evidence from the Nordic Stock Exchanges

Abstract: The purpose of this study is to explore the volatility and secondary effects in the four Nordic stock exchanges of Norway: Oslo Børs Linked all-share index AXLT Denmark: OMX Copenhagen 20, Sweden: OMX Stockholm 30 and Finland: OMX Helsinki 25. Keeping in mind that there is an ARCH effect in the returns of the four stock exchanges, we move on to the evaluation to the evaluation of models ARCH (q), GARCH (p, q) και GARCH-M (p, q). Evaluating the parameters became possible through the use of the maximum likelihoo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 14 publications
0
2
0
1
Order By: Relevance
“…We compare the test results to previous studies which adopted similar empirical strategies on Scandinavian stock markets, and find that the volatility pattern of the Swedish real estate sector-leverage effect and long-range dependence specifically-follow similar movement of the stock market as a whole [34][35][36][37]. Further, the Swedish Real Estate Sector Index's average mean-reverting half-life period is 49 days, which is longer than other developed markets such as NYSE Composite and Nikkei [63], but faster than emerging markets such as the Saudi Stock Exchange (30 months) [62].…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…We compare the test results to previous studies which adopted similar empirical strategies on Scandinavian stock markets, and find that the volatility pattern of the Swedish real estate sector-leverage effect and long-range dependence specifically-follow similar movement of the stock market as a whole [34][35][36][37]. Further, the Swedish Real Estate Sector Index's average mean-reverting half-life period is 49 days, which is longer than other developed markets such as NYSE Composite and Nikkei [63], but faster than emerging markets such as the Saudi Stock Exchange (30 months) [62].…”
Section: Discussionmentioning
confidence: 90%
“…Empirical volatility studies of the Scandinavian region are limited. Dritsakis and Savvas [34] explored the volatility of four Nordic stock exchanges in Norway, Denmark, Sweden, and Finland using ARCH (q), GARCH (p, q), and GARCH-M(p, q) models, which were evaluated through MSE, MAE, RMSE, and MAPE. They found that ARMA (0, 1)-GARCH-M (1, 1) and ARMA (0, 3)-GARCH (1, 1) models are the most accurate in terms of Student's-t distribution.…”
Section: Review Of Volatility Patternsmentioning
confidence: 99%
“…Imbal hasil saham merupakan salah satu topik penting dalam dunia ekonomi. Evaluasi terhadap suatu aset dapat dilakukan dengan menggunakan imbal hasil saham tersebut, yang secara konvensional didefinisikan sebagai fungsi logaritma natural terhadap perubahan harga [1]. Namun, apakah imbal hasil saham di masa depan dapat diduga menjadi pertanyaan yang krusial dikemukakan oleh Ding, et.al [2].…”
Section: Pendahuluanunclassified